Identifying genetic variants associated with amphotericin B (AMB) resistance in Aspergillus fumigatus via k-mer-based GWAS - Chen, Meng-Meng; Shi, Guo-Hui; Dai, Yi; Fang, Wen-Xia; Wu, Qi (Frontiers in Genetics, 2023)
Aspergillus fumigatus is one of the most common pathogenic fungi, which resulted in high morbidity and mortality in immunocompromised patients. Amphotericin B (AMB) is used as the core drug for the treatment of triazole-resistant A. fumigatus. Following the usage of AMB drugs, the number of AMB-resistant A. fumigatus isolates showed an increased trend over the years, but the mechanism and the mutations associated with AMB sensitivity are not fully understood. In this study, we performed a k-mer-based genome-wide association study (GWAS) in 98 A. fumigatus isolates from public databases. Associations identified with k-mers not only recapitulate those with SNPs, but also discovered new associations with insertion/deletion (indel). Compared to SNP sites, the indel showed a stronger association with AMB resistance, and a significant correlated indel is present in the exon region of AFUA_7G05160, encoding a fumarylacetoacetate hydrolase (FAH) family protein. Enrichment analysis revealed sphingolipid synthesis and transmembrane transport may be related to the resistance of A. fumigatus to AMB. The expansion of variant types detected by the k-mer method increases opportunities to identify and exploit complex genetic variants that drive AMB resistance, and these candidate variants help accelerate the selection of prospective gene markers for AMB resistance screening in A. fumigatus.